AUDIT OPERASIONAL DALAM PENILAIAN KINERJA FUNGSI PELAYANAN PADA TICKETING PT SRIWIJAYA AIR - Kumalayanti, Cindi Claudya; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purposes of this research i.e.: (1) to understand the role of operational audit in improving the service functions effectively and efficiency of service and (2) to analyze some factors which have caused the effectiveness and the efficiency of performance in service department. The data analysis technique has been done by using descriptive analysis and the qualitative analysis approach by collecting the required data which is related to the operational audit of the service function in Sriwijaya Air Distrik Surabaya. The result of the research shows that the problems that have been encountered by Sriwijaya Air Distrik Surabaya is the performance and the attitude as the ticketing officer cannot besaid to be very good because to behave and to deal with prospective passengers the ticketing officer does not implement the principle of respect and joke in front of the passengers can make bad image to the company. But, in general, the implementation of the service activities in Sriwijaya Air Distrik Surabaya have been running effectively and efficiently and have met the standard service procedures of Sriwijaya Air which have becomes the guide lines of the company.Keywords: Operational Audit, Service Function, Effectiveness and Efficiency.